2014 IEEE International Conference on Imaging Systems and Techniques (IST) Proceedings 2014
DOI: 10.1109/ist.2014.6958500
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the performance of a CAD<inf>x</inf> scheme for mammography in specific BIRADS categories

Abstract: A Computer Aided Diagnosis (CAD x ) pipeline has already been introduced to discriminate between benign and malignant clusters of microcalcifications (MCs). In this study, we evaluate the specific methodologies using cases from publicly available databases of mammograms, the MIAS database and the Digital Database of Screening Mammography (DDSM). Specifically, we investigate various subsets of regions of interest (ROIs) containing cluster of MCs, following the BIRADS assessment performed by radiologists who hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In a previous study [19], we indicated that CAD x methodologies perform satisfactorily in subsets of obscure cases (such as BIRADS 3), where the radiologists recommend a short follow-up. This observation implies that such 'oriented' schemes, following radiologist's BIRADS assessment, may be adopted during the diagnostic process to assist expert's diagnosis.…”
Section: List Of Cad X Schemesmentioning
confidence: 86%
“…In a previous study [19], we indicated that CAD x methodologies perform satisfactorily in subsets of obscure cases (such as BIRADS 3), where the radiologists recommend a short follow-up. This observation implies that such 'oriented' schemes, following radiologist's BIRADS assessment, may be adopted during the diagnostic process to assist expert's diagnosis.…”
Section: List Of Cad X Schemesmentioning
confidence: 86%
“…Studies from the literature have shown that a double reading from two independent radiologists can improve the diagnosis of breast lesions [18][19][20][21]; however, a double check has a high operational cost in terms of resource utilization and time, thus preventing its application in broader healthcare settings. In this sense, CAD systems, along with reproducible and standardized radiomics workflows, could offer the opportunity to obtain a "second opinion" from an automated tool, thus improving the diagnostic accuracy with less operational cost and within a reduced timeframe [22,23]. The sensitivity of such automated tools, i.e., the ability to find and properly characterize suspicious areas, is, therefore, of fundamental importance to increase the reliability and clinical translation of CAD systems and radiomics workflows in most radiology applications [24][25][26][27][28][29][30][31][32], which can be then combined with artificial intelligence (AI) approaches, such as machine learning (ML) and deep learning (DL) techniques, to further boost the automated diagnostic performance [33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%